Linux shell scripting : a project-based approach to learning - Cannon, Jason (Packt Publishing, 2018)
"Have you tried to learn shell scripting on your own, but lack the structure you need to really improve your skills? Are you tired of picking up bits and pieces of information that you can't just seem to put together? Do you learn best by doing? If so, you're going to love this course. One of the biggest complaints I hear from students is that most of the courses they've taken in the past simply provide information without any context and without any idea of how to put that information to use! This course turns that old, frustrating, and outdated way of learning on its head. It's project-based, which means that, instead of learning bits and pieces of information, you'll write actual shell scripts that you can use in real-world situations. You get the chance to immediately put what you learn to use so that you fully understand and remember it. If you're ready to level-up your shell scripting skills, enroll now!"--Resource description page